Out in Front: Government Regulation of Television in Malaysia: Government Regulation - Kitley, Philip; Nain, Zaharom (Television, Regulation and Civil Society in Asia, 2002)
Modern Malaysia was established in 1963 following a drawn-out struggle against British interests which had occupied territory on Penang and Singapore and the Straits of Malacca in 1786, 1819 and 1824 respectively. In 1867 these outposts came under the control of the British Colonial Office and were governed as a Crown Colony. Although Britain did not directly colonise the Malay States, which remained legally autonomous, it imposed effective administrative control over Malaya and the Borneo territories from the late 1870s until the Japanese occupation in 1942.
Keywords: 1-TV; 2-Approches sociologiques; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Étude des industries culturelles; 3-Asie (corpus analysé); 4-Europe (lieu de production du savoir); 4-Océanie (lieu de production du savoir); 5-Auteur.rice PANDC; Australie (lieu de production du savoir); Malaisie (corpus analysé); Royaume-Uni (lieu de production du savoir); _Nettoyé

Bowling with the Wind: A Television Producer’s View on Cricket and Satellite TV in Contemporary India - Hutton, Peter (Television in India: Satellites, Politics and Cultural Change, 2008)
Growing up in England, it never really occurred to me to wonder why Inever saw cricket from India on television. Indian cricket was always insight; we had Bishen Singh Bedi in his mysterious headgear wheeling in forNorthamptonshire, Srinivas Venkatraghavan wrapped in sweaters at Derby,Madan Lal playing in front of handfuls of old men in the Yorkshire leagues.Yet the Packer ‘circus’ largely left India alone, and in England the touringIndian side became an unglamorous pause between the glorious tours bythe West Indies and Australia. Little was I to guess that once I started working in television, India would become central to the world cricketeconomy and crucial to the technological improvements in the coverage ofthe game.
Keywords: 1-TV; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Étude des industries culturelles; 3-Asie (corpus analysé); 4-Europe (lieu de production du savoir); Inde (corpus analysé); Royaume-Uni (lieu de production du savoir); _Nettoyé

Analysing How Zimbabwe Broadcasting Corporation (ZBC TV) and Eswatini TV (ESTV) Are Adapting to the Digital Era - Lunga, Carolyne M.; Musvipwa, Rosemary (Television in Africa in the Digital Age, 2021)
The internet has impacted on how media organisations do journalism. Many media organisations both print and broadcast now have an online presence to reach out to fragmented audiences that have migrated to online platforms. Television stations have increasingly embraced the use of digital (online) media to gain better access to their audiences in terms of content distribution and audience engagement. The rise of social media platforms such as Facebook, Twitter, YouTube and Instagram have given journalists and media organisations the ability to reach their audiences immediately, with the added beneﬁt of audience responses which come almost immediately. The use of new digital media has created platforms for news stations to share digital clips of news items or excerpts of news programmes to keep the audiences informed or enticed by the highlights.
Keywords: 1-TV; 2-Approches sociologiques; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Étude des industries culturelles; 3-Afrique (corpus analysé); 4-Afrique (lieu de production du savoir); 4-Europe (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Auteur.rice noir.e; 5-Autrice; Eswatini (corpus analysé); Eswatini (lieu de production du savoir); Royaume-Uni (lieu de production du savoir); Zimbabwe (corpus analysé); _Nettoyé

Entertaining Africans: Creative Innovation in the (Internet) Television Space - Dovey, Lindiwe (Television in Africa in the Digital Age, 2021)
Despite great heterogeneity, the vast continent of Africa and the diverse people of its countries and diasporas have often been represented through the most reductive, essentialising, and denigrating paradigms— a process that Nigerian writer Chimamanda Adichie Ngozi has referred to as “the danger of a single story”. One of the most dangerous of these paradigms is the developmentalist one, which shoehorns Africa into a western, capitalist teleological framework that overlooks and denies Africa’s production of and participation in forms of leisure, pleasure and entertainment.
Keywords: 1-TV; 2-Analyses formalistes; 2-Approches sociologiques; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Étude de la réception; 3-Afrique (corpus analysé); 3-Europe (corpus analysé); 4-Europe (lieu de production du savoir); 5-Autrice; 5-Identités diasporiques; Royaume-Uni (corpus analysé); Royaume-Uni (lieu de production du savoir); _Nettoyé

Defining the Nation?: Lebanese Television and Political Elites (1990–2005) - Nötzold, Katharina (Frank & Timme, 2013)
Katharina Nötzold explores whether and how mass media can contribute to nation-building after civil war. Drawing on the example of Lebanon’s audiovisual media organisations, which are mostly privately owned by politicians, she demonstrates how political elites use television to transmit their visions of post-war society. Lebanon’s nation-building process from 1990 to 2005 was characterized by Syrian dominance over political life. From an extensive content analysis of Lebanese news and interviews with analysts, journalists and managers from all Lebanese TV stations, it emerges that political information on television focused more on divisive experiences than cohesive ones. This has underpinned continued sectarianism in Lebanon, in the media as in society at large, and has impeded nation-building. Biographische Informationen Katharina Nötzold is a political scientist and RCUK Research Fellow at the University of Westminster's Arab Media Centre, and she completed her PhD in Media and Communications at the University of Erfurt, Germany. She lived in Beirut and Amman and worked previously for the Center for International Peace Operations, Berlin. She is editor of Westminster Papers in Communication and Culture and author of articles on Arab media and media representations of migrants and Islam. Reihe Medien und politische Kommunikation – Naher Osten und islamische Welt - Band 19
Keywords: 1-TV; 2-Approches sociologiques; 2-Histoire/Historiographie critique; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Étude des industries culturelles; 3-Asie (corpus analysé); 4-Europe (lieu de production du savoir); 5-Autrice; Allemagne (lieu de production du savoir); Liban (corpus analysé); _Nettoyé

Watching Si Doel: Television, Language and Identity in Contemporary Indonesia - Loven, Klarijn (BRILL, 2008)
While television in today's world increasingly displays a global character, national television systems are still firmly rooted in a specific locality. But in what ways does this locality actually shape the content and performance of national television? What is the significance of local cultures and local languages in these processes of mediation? And how do the local, the national, and the global intersect in discourses of and discourse on television? Taking a critical discourse analysis perspective, Watching Si Doel investigates these and related questions in the context of contemporary Indonesia. Starting from the nationwide popularity of the local television serial Si Doel Anak Sekolahan ("Educated Doel"), it examines the various ways in which the national government, Indonesian television producers, and local audiences shape, interpret, and struggle over the meaning of the phrase 'national television'. In doing so, the book explores what Indonesian television at the turn of the century sounds and looks like--and, significantly, ought to sound and look like--according to those who create and control television and those who watch and interpret it. While providing insight into the production, nature, and reception of television discourse in general, this book particularly seeks to clarify the relationship between television, language, and power in late New Order and post-Soeharto Indonesia.
Keywords: 1-TV; 2-Approches sociologiques; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Étude de la réception; 2-Étude des industries culturelles; 2-Étude des représentations; 3-Asie (corpus analysé); 4-Europe (lieu de production du savoir); 5-Autrice; Indonésie (corpus analysé); Pays-Bas (lieu de production du savoir); _Nettoyé

Visual Political Communication in Popular Chinese Television Series - Schneider, Florian; Dudbridge, Glen; Pieke, Frank N. (BRILL, 2012)
In Visual Political Communication in Popular Chinese Television Series, Florian Schneider analyses political discourses in Chinese TV dramas, the most popular entertainment format in China today.
Keywords: 1-TV; 2-Approches sociologiques; 2-Histoire/Historiographie critique; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Étude des industries culturelles; 2-Étude des représentations; 3-Asie (corpus analysé); 4-Europe (lieu de production du savoir); Chine (corpus analysé); Pays-Bas (lieu de production du savoir); Royaume-Uni (lieu de production du savoir); _Nettoyé

From TRT to Netflix: Implications of Convergence for Television Dramas in Turkey - Yanardağoğlu, Eylem; Turhallı, Neval (Television in Turkey: Local Production, Transnational Expansion and Political Aspirations, 2020)
Since the1980s, the television (TV) drama has proved to be one of the most dominant formats on Turkish TV channels and occupied major slots on primetime throughout the 1990s and 2000s. As Internet penetration grew, on-demand services transformed audiences’ expectations of TV series. Internet series first became a trend on YouTube in 2013, and Netflix began broadcasting in Turkey at the beginning of 2016. Its entry to the sector triggered video-on-demand suppliers like Blu TV and Puhu TV which are digital enterprises of Doğan and Doğusṃ Holdings. Blu TV announced their first original project in 2017, Masum (Innocent), which was a big-budget series that included famous actors. In the same year, Puhu TV released their first original, Fi (Phi). Finally, Netflix launched their first original production in Turkey, Hakan: The Protector, in 2018. This chapter focuses on the implications of convergence for the production and distribution of TV dramas and considers the changes in the sector as television broadcasting shifted to new media platforms in Turkey.
Keywords: 1-TV; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Étude des industries culturelles; 3-Asie (corpus analysé); 3-Europe (corpus analysé); 4-Asie (lieu de production du savoir); 4-Europe (lieu de production du savoir); 5-Auteur.rice; 5-Auteur.rice PANDC; Turquie (corpus analysé); Turquie (lieu de production du savoir); _Nettoyé

Mediatisation and Hyper-commodification of Sport in Post-1980 Turkey - Irak, Dağhan (Television in Turkey: Local Production, Transnational Expansion and Political Aspirations, 2020)
Sport has had a symbiotic relationship with television for decades, as it has always been one of the most marketable visual products for the medium. The new visual media technologies that have been introduced since the 1970s have altered this relationship greatly by incrementally commodifying sport at each step. One of the most crucial aspects of this relationship is globalisation, which initially depended on satellite television and took sport’s hyper-commodification to a whole new level. Turkey, which went through a massive transformation to a neoliberal rule following a bloody coup d’etat in 1980 that practically razed the whole social and political structure, has since become an important example of the roles of sport and television in an aggressively neoliberal setting. This chapter aims to explain why televised sport has had a remarkable role in the sociopolitical transformation of Turkey since the 1980 coup.
Keywords: 1-TV; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Étude des industries culturelles; 3-Asie (corpus analysé); 3-Europe (corpus analysé); 4-Europe (lieu de production du savoir); Royaume-Uni (lieu de production du savoir); Turquie (corpus analysé); _Nettoyé

Continuities and Changes in the Transnational Broadcasts of TRT - Karanfil, Gökçen (Television in Turkey: Local Production, Transnational Expansion and Political Aspirations, 2020)
This chapter traces the evolution of the Turkish Public Service Broadcaster with a focus on its transnationalization. Drawing parallels between the changing dynamics in politics, culture, and media in Turkey; contemporary cosmopolitan media cultures; and the continuities and changes in Turkish Radio and Television Corporation’s (henceforth TRT) identity as a public service broadcaster, I shed light on the ways in which TRT has been engaging in transnational broadcasts since the beginning of 1990s. For this I elaborate on the ways in which transnational broadcasting processes in Turkey have been influenced by media transnationalization around the world. I discuss two different incentives behind TRT’s transnational endeavors. First, I elaborate on TRT’s attempts at engaging with the Turkish diaspora around the world; later, I articulate how, in more recent years, TRT sets out to exert a Turkish cultural presence in the Middle East and North Africa (MENA) region. The chapter aims to draw a general portrait of the concept of transnational broadcasting in Turkey with a specific focus on the country’s public service broadcaster, TRT.
Keywords: 1-TV; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Étude des industries culturelles; 3-Asie (corpus analysé); 3-Europe (corpus analysé); 4-Asie (lieu de production du savoir); 4-Europe (lieu de production du savoir); 5-Auteur.rice PANDC; Turquie (corpus analysé); Turquie (lieu de production du savoir); _Nettoyé

Televised Journalistic Documentaries of the 1990s: The Form, Content, and Historical Juncture - Çelik, Burçe (Television in Turkey: Local Production, Transnational Expansion and Political Aspirations, 2020)
The 1990s’ popular televised journalistic/history documentaries have played a vital role in the making of political television culture, society of political spectacle, and the production of popular history and memory in Turkey. Despite their importance, these documentaries did not attract enough scholarly attention. By focusing on arguably the most popular and impactful journalistic/history documentaries of Turkey’s history, developed by Mehmet Ali Birand in the 1990s, I will assess the role of television in teaching, telling, and writing the political history. In doing so, I will also contextualize the form and discourse of these documentary series within historical juncture of globalization and neoliberalization of television as well as the country’s political economy.
Keywords: 1-TV; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Étude des industries culturelles; 3-Asie (corpus analysé); 3-Europe (corpus analysé); 4-Europe (lieu de production du savoir); 5-Auteur.rice; 5-Auteur.rice PANDC; Royaume-Uni (lieu de production du savoir); Turquie (corpus analysé); _Nettoyé

The Regulation of Television Content in Turkey: From State Monopoly to Commercial Broadcasting and Beyond - Sümer, Burcu; Taş, Oğuzhan (Television in Turkey: Local Production, Transnational Expansion and Political Aspirations, 2020)
In contrast with radio broadcasting, which began in 1927, television started remarkably late in Turkey. When the country’s sole public service broadcaster, Turkish Radio and Television Corporation (TRT), was established in 1964 and all of the radio transmitters were transferred to the Corporation, even radio broadcasting was not successfully institutionalized to catch up with its Western counterparts. For a very young Republic like Turkey, radio was an integral part of the modernization and nation-building agenda of the early ruling elite and therefore it institutionalized as a part of the machinery of the state, under very strict state control. Much known indispensable merits of autonomy and independence attributed to the historical public service broadcasting model in Europe were hardly appreciated and supported in Turkey. Television broadcasting also had its share from this negative perception and had to face similar obstructions as radio from the beginning. This chapter traces the history of content regulation in television broadcasting by situating the political controversies at the center at different times from the 1960s until today. Unfortunately, as the saying goes, there is nothing new under the sun, not in Turkey.
Keywords: 1-TV; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Étude des industries culturelles; 3-Asie (corpus analysé); 3-Europe (corpus analysé); 4-Asie (lieu de production du savoir); 4-Europe (lieu de production du savoir); 5-Auteur.rice; 5-Auteur.rice PANDC; Turquie (corpus analysé); Turquie (lieu de production du savoir); _Nettoyé

Structural Changes in the Ibero-American TV Market: Concentration and Convergence against Diversity? - Mastrini, Guillermo; Leiva, María Trinidad García (The Routledge Companion to Global Television, 2019)
This chapter examines the structural changes that can be identified in Ibero-American television in the first 15 years of the 21st century. Taking as a reference the main TV markets in the region (Mexico, Brazil, Argentina and Spain) and their peculiar historical developments, a brief introduction and overview describes their characteristics, potentials and limitations, underlining their strengths, weaknesses and challenges. The analysis, framed in the globalizing phase that cultural products and services are undergoing jointly with their increased digitization, suggests two fundamental drivers of change, summarized in the notions of concentration and convergence. To conclude, policies and recommendations for action are explored, with a view to promote and protect audiovisual diversity.
Keywords: 1-TV; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Étude des industries culturelles; 3-Amérique du Sud (corpus analysé); 4-Amérique du Sud (lieu de production du savoir); 4-Europe (lieu de production du savoir); 5-Auteur.rice; 5-Auteur.rice PANDC; Argentine (corpus analysé); Argentine (lieu de production du savoir); Brésil (corpus analysé); Espagne (corpus analysé); Espagne (lieu de production du savoir); Mexique (corpus analysé); _Nettoyé

Telenovela, an Instrument for Democracy - Eskandari, Sina (Review of European Studies, 2017)
Telenovela shapes important and highly favorite section of the television productions. The T.V. series have moved out from their traditional structure with an entertaining aspect and have been divided into different types and scopes. Taking into consideration the time and the atmosphere of dissemination which the Telenovela programs hold in T.V. antenna, there is a need to conduct studies on sociology of Telenovela more than any other times in the past. This article is an attempt to review the two subject-matters of Telenovela and Narration and their connection with democracy through sociological sporadic studies. This will also present the significance of this genre in T.V. productions at local and international discourses. Observations, field researches and library study methods have been employed in this research.
Keywords: 1-TV; 2-Approches sociologiques; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Étude de la réception; 3-Amérique du Sud (corpus analysé); 4-Europe (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Identités diasporiques; Colombie (corpus analysé); Espagne (lieu de production du savoir); _Nettoyé